DIRECTIONS FOR OPTIMIZING LOCAL BUDGETS IN THE SUSTAINABLE DEVELOPMENT OF REGIONS - Kholboyev Abdurakhmon Shokirovich (Journals Park Publishing, 2023)
This article consists of developing a scientific proposal and practical recommendations aimed at improving the medium-term planning of local budgets for the purpose of social and infrastructural development of the regions. Also, as a result of today's analysis of the local budget revenues of Uzbekistan, scientific proposals and recommendations have been formed to further increase them, reduce budget risks and optimize costs.
Keywords: budget, budget classification, local budget, state budget, budget risk, budget deficit, budget surplus, expenditure, income, budget planning.